Motor Stereotypic Behavior Was Associated With Immune Response in Macaques: Insight From Transcriptome and Gut Microbiota Analysis - Pan, Xuan; Liu, Fangyuan; Song, Yang; Wang, Hongrun; Wang, Lingyun; Qiu, Hong; Price, Megan; Li, Jing (Frontiers in Microbiology, 2021)
Motor stereotypic behaviors (MSB) are common in captive rhesus macaques (Macaca mulatta) and human with psychiatric diseases. However, large gaps remain in our understanding of the molecular mechanisms that mediate this behavior, and whether there are similarities between human and non-human primates that exhibit this behavior, especially at gene expression and gut microbiota levels. The present study combined behavior, blood transcriptome and gut microbiota data of two groups of captive macaques to explore this issue (i.e. MSB macaques with high MSB exhibition and those with low: control macaques). Observation data showed that MSB macaques spent the most time on MSB (33.95%), while the CONTROL macaques allocated more time to active (30.99%) and general behavior (30.0%), and only 0.97% of their time for MSB. Blood transcriptome analysis revealed 382 differentially expressed genes between the two groups, with 339 up-regulated genes significantly enriched in inflammation/immune response-related pathway. We also identified up-regulated pro-inflammatory genes TNFRSF1A, IL1R1 and IL6R. Protein-protein interaction network analysis screened nine hub genes that were all related to innate immune response, and our transcriptomic results were highly similar to findings in human psychiatric disorders. We found that there were significant differences in beta-diversity of gut microbiota between MSB and CONTROL macaques. Of which Phascolarctobacterium, the producer of short chain fatty acids (SCFAs), was less abundant in MSB macaques. Meanwhile, PICRUSTs predicted that SCFAs intermediates biosynthesis and metabolic pathways were significantly down-regulated in MSB macaques. Together, our study revealed that the behavioral, gene expression levels and gut microbiota composition in MSB macaques was different to controls, and MSB was closely linked with inflammation and immune response. This work provides valuable information for future in-depth investigation of MSB and human psychiatric diseases.